Investigation of the occurrence characteristics of organic components in high-sulfur waste residues (HSWR) - Wang, Zhongbing; Jie, Fanghui; Li, Weiqi; Zhao, Zongwen; Niu, Fei; Zhu, Junqiang; Qin, Weining; Zhou, Kai (Frontiers in Environmental Science, 2022)
High-sulfur waste residue (HSWR) is a typical byproduct produced in the printing and dyeing industry that has hazardous properties, such as flammability and reactivity, etc. It is of great significance for the directional and harmless treatment of waste residues in the later stage on the research in-depth of the occurrence characteristics of each component in HSWR. In this paper, the combinatorial analysis method is employed to perform in-depth research on the phase composition, surface chemical situation of element, and the occurrence state of functional groups of the waste residue from multiple perspectives. The results show that the organic and inorganic components in HSWR are intricately interwoven, and exhibit significant thermal instability at high temperatures, with a maximum weight less of 86.66%. Carbon mainly exists in the states of C-H/C-OH/C-C, C-O/C-NH2, and C=O/C-N/C-S/CHx and constitutes the main chain of the carboxylic ring. Sulfur mainly occurs in three forms, namely, amorphous aggregated sulfur, sulfur-containing inorganic salts such as sulfate, and nitrogen-heterocyclic organic compounds containing sulfhydryl groups and methyl sulfur groups. These organic compounds constitute branch chains of the organic phase, and combine with metal cations through hydroxyl or carboxyl groups, and deposit on the surface of inorganic agglomerated sulfur. This wrapping structure increases the stability of volatile compounds in the slag and increases the difficulty of sulfur and chlorine removal. These findings provide a material basis for the later development of safe and effective HSWR disposal techniques.